PRODUCTION, ISOTOPIC COMPOSITION, AND ATMOSPHERIC FATE OF BIOLOGICALLY PRODUCED NITROUS OXIDE - Stein L.Y.; Yung Y.L. (My University, 2003)
The anthropogenic production of greenhouse gases and their consequent effects on global climate have garnered international attention for years. A remaining challenge facing scientists is to unambiguously quantify both sources and sinks of targeted gases. Microbiological metabolism accounts for the largest source of nitrous oxide (N2O), mostly due to global conversion of land for agriculture and massive usage of nitrogen-based fertilizers. A most powerful method for characterizing the sources of N2O lies in its multi-isotope signature. This review summarizes mechanisms that lead to biological N2O production and how discriminate placement of 15N into molecules of N2O occurs. Through direct measurements and atmospheric modeling, we can now place a constraint on the isotopic composition of biological sources of N2O and trace its fate in the atmosphere. This powerful interdisciplinary combination of biology and atmospheric chemistry is rapidly advancing the closure of the global N2O budget.
Keywords: microorganisms; isotopic discrimination; photolysis; greenhouse gas; global budget